Comparison of blood glucose level between breast–fed and formula–fed term babies - Omar Sazali Aldy; Bugis M Lubis; Pertin Sianturi; Emil Azlin; Guslihan D. Tjipta (Indonesian Pediatric Society, 2008)
Background Hypoglycemia is common in newborns in the firstfew hours after birth. This may also occur in term babies. Dataof hypoglycemia in breastfed and formula-fed infants have beenlimited.Objective To compare blood glucose levels between breast-fed andformula-fed healthy term babies at 1, 24 and 48 hours of life.Methods A cross sectional study was performed on 32 neonatesbetween January and March 2007 in the Dr. Pirngadi Hospital.The subjects was classified into two groups, the breastfed andformula-fed groups. Blood glucose level was examined at 1, 24,and 48 hours after birth and level ofless than 2.6 mmol/1 definedthe presence of hypoglycemia.Results There was statistically significant difference in meanblood glucose level at 1 hour of life between breastfed [59.25(SD 3.38) mg/dl] and formula-fed infants [55.96 (SD 8.60) mg/dl], (P=0.049), while no significant difference was found after24 hours of life, i.e., 62.59 (SD 3.57) mg/dl vs. 61.21 (SD 6.87)mg/dl, P=0.319 and also after 48 hours of life, i.e., 67.34 (SD5.18) mg/dl vs. 66.75 (SD 7.76) mg/dl, P=0.720.Conclusion The blood glucose level at one hour after birth wassignificantly different in breastfed compared to formula-fed infants,while no statistically significant difference was found at 24 hoursand 48 hours after birth. The mean blood glucose at 24 hours oflife was lower than that of 48 hours after birth